Analysis of Endurance Training in Volleyball: A Systematic Literature Review - Rafi Tri Indarwan; Adi S (Indonesian Journal for Physical Education and Sport, 2025)
The purpose of this study is to examine the use of endurance training in Volleyball. Materials and methods: The PRISMA table will be used for systematic review and meta-analysis in this review investigation. Various studies were published from 2020 to 2025. In the search procedure, the following keywords were used: (1) Analysis; (2 Endurance); (3) Volleyball. The search in this study used the Scopus research journal database. The overall theme of this study obtained 170 articles. Contains 63 articles, of which 10 were used in this study. The analysis of endurance training in volleyball includes the effect of endurance training based on relevant results, including increasing vertical jumps, improving performance, and significantly increasing the endurance of volleyball players.